Correlation of serum follicular stimulating hormone (FSH) and luteinizing hormone (LH) as measured by radioimmunoassay in disorders of sexual development - Penny, Robert (1970)
Serum FSH and LH levels in 104 patients with disorders of sexual development were determined by radioimmunoassay and compared with serum FSH and LH levels in 164 normal individuals. 32 of 35 gonadal dysgenesis patients (ages 4.8-18.9 yr) had serum FSH levels which were elevated above the range of normal for chronological age, and 19 had serum LH levels similarly elevated. All patients with elevated serum LH levels were 11 yr of age or older. However, 8 of 10 gonadal dysgenesis patients, ages 4.8-10.9 yr, had serum FSH levels elevated above the normal range. In accord with these observations was the finding that in normal girls, serum FSH levels may increase at an earlier age than do serum LH levels (FSH, 5-8 yr of age; LH, 9-10 yr of age). These data indicate that serum FSH determinations may be helpful in diagnosing gonadal dysgenesis during childhood. Serum gonadotropin levels within the range of normal for chronological age were found in 2 of 18 girls with idiopathic isosexual precocity. The other 16 had serum FSH levels elevated above the range of normal for chronological age, and 8 also had serum LH levels similarly elevated. In all instances serum FSH and LH levels were in the range expected for the stage of sexual development. In 35 boys, ages 13.1-17.8 yr, with delayed adolescence, serum gonadotropin levels correlated with stage of sexual development and, therefore, were often less than those expected for age. 8 patients with premature pubarche, 5 patients with premature thelarche, and 3 patients with adolescent gynecomastia had serum gonadotropin levels within the range of normal for chronological age.